EP370 The efficacy of hysterectomy for local remnant or recurrent cervical cancer after radical radiotherapy. (1st November 2019) - Nakasone, T; Shimoji, Y; Arakaki, Y; Taira, Y; Nakamoto, T; Oyama, T; Kudaka, W; Aoki, Y
Abstract : Introduction/Background: Radiation therapy is an effective treatment for cervical cancer (CC), but remains at a constant rate, and those cases have a poor prognosis. The purpose of this study was to examine the efficacy of adjuvant hysterectomy in local remnant or recurrent (LR) cases of CC after radical radiotherapy (RT). Methodology: Between May 2007 and September 2018, 21 patients who underwent hysterectomy for LR CC after RT in our department were included in this study. We retrospectively reviewed their medical records for patient background, clinicopathological factors, complications and prognosis. LR CC was determined based on histopathological and imaging examinations 3 months after the end of treatment. We classified surgical specimens according to the treatment effect (effects 0–3) using histological effect criteria. In addition, we used the Kaplan-Meier and log-rank test for statistical analyses. Results: The median patient age was 55 years, and the FIGO stages were IB2, IIB and IIIB in 11, 8 and 2 cases, respectively. Based on the histological type, there were 14 cases of squamous cell carcinoma and 7 of adenocarcinoma. Tumour markers (TM) were re-elevated in five cases. Perioperative complications included intraoperative bladder injury and postoperative pelvic abscess in two cases. The median observation period was 39 months, and there were 10 recurrences. The median progression-free survival (PFS) was 54 months, and the 3-year overall survival (OS) rate was 61.1%. With regard to prognostic factors, the treatment effect (effect 1 vs. effect 2/3) was significantly associated with PFS (p=0.008) and OS (p=0.023) and the re-elevation of TM was significantly associated with PFS (p=0.017). Conclusion: Hysterectomy for LR CC after RT might be a tolerable treatment with a long-term prognosis. Histological treatment effect evaluation of surgical specimens might be useful in additional treatment assessment, and TM elevation might be useful in preoperative assessment. Disclosure: Nothing to disclose.